Media violence: The effects are both real and strong - Murray, John P. (My University, 2008)
Fifty years of research on the effect of TV violence on children leads to the inescapable conclusion that viewing media violence is related to increases in aggressive attitudes, values, and behaviors. The changes in aggression are both short term and long term, and these changes may be mediated by neurological changes in the young viewer. The effects of media violence are both real and strong and are confirmed by the careful reviews of research evidence by various scientific and professional organizations that are concerned with children's mental health and development.
Keywords: Children; Neurological effects; Television; Violence